Quality Management of Human Resource Development in Realizing Globally Competitive Islamic Educational Institutions - Zainal Arifin; Rahmat Ridwan; S. Ali Jadid Alaydrus; Maimun Maimun (Jurnal Ilmiah Profesi Pendidikan, 2025)
This study examines the implementation of quality management in human resource development as a strategic approach to enhancing the global competitiveness of Islamic educational institutions. In the context of increasingly complex educational challenges driven by globalization, technological advancement, and shifting labor market demands, Islamic educational institutions are required to strengthen the competence, professionalism, and spiritual integrity of their human resources. This research aims to analyze how quality management principles-encompassing planning, implementation, evaluation, and continuous improvement-are conceptualized and practiced in the development of educators and educational staff to achieve institutional excellence. The study employs a qualitative descriptive library research approach, drawing on systematic analysis of scholarly journal articles, academic books, policy documents, and authoritative literature related to Total Quality Management (TQM), human resource development, and Islamic education management. Data were examined using thematic content analysis to identify key patterns, strategies, and conceptual linkages across sources. The findings indicate that the integration of TQM principles with Islamic ethical values effectively fosters a culture of professionalism, accountability, continuous learning, and ethical leadership. Human resource development initiatives emphasizing competency-based training, spiritual character cultivation, formative evaluation, and participatory management contribute significantly to improved educational quality and institutional adaptability. Furthermore, alignment between modern quality management practices and Islamic moral principles strengthens organizational commitment and supports the formation of globally competitive graduates who embody both intellectual capability ('ilm) and moral integrity (akhlaq). The study concludes that quality management of human resource development constitutes a fundamental pillar for transforming Islamic educational institutions into globally competitive entities while preserving their distinctive spiritual and ethical identity.